Improving Aesthetic Leaf Quality of Sansevieria through Natural Plant Growth Regulators in Soilless Art Glass Cultivation - Ika Jannatul Afifah; Ilham Rahmanov (Athallah Publishing globalindo, 2026)
This study aimed to determine the effect of natural plant growth regulators (PGRs) derived from seaweed extract on soilless growing media in enhancing the visual quality of Sansevieria ornamental plant leaves using the art glassplanting technique. The main problems in this technique include limited nutrients, low light intensity, and the absence of growth regulators in the medium, which lead to reduced aesthetics and leaf color quality. The research was conducted using an experimental method with a Completely Randomized Design (CRD), consisting of six concentrations of seaweed extract (0%, 50%, 55%, 60%, 65%, and 70%) with four replications. Observed parameters included leaf aesthetics (shape, thickness, symmetry, texture, and integrity) and leaf color quality (L*, a*, and b* values). ANOVA results showed that the application of seaweed extract had a significant effect on all aesthetic parameters (p < 0.05), with the 70% concentration yielding the highest values. Leaf color observation indicated that the 70% concentration produced a darker green color, as shown by the decrease in L*, a*, and b* values. This confirms an increase in chlorophyll content and visual quality of the leaves. Therefore, seaweed extract is proven to be an effective natural PGR for improving the aesthetic and physiological appearance of Sansevieria leaves in soilless art glassplanting systems.